The Development of PISA-based Numerical Problem Using the Context of Religious Day during the Pandemic - Sepriliani, Sisca Puspita; Zulkardi; Putri, Ratu Ilma Indra; Samsuryadi; Alwi, Zahra; Meryansumayeka; Jayanti; Nusantara, Duano Sapta; Sistyawati, Risda Intan; Tanjung, Ayu Luviyanti; Aprilisa, Shinta; Pratiwi, Riszky Pabela (Mathematics Education Journal, 2022)
This study aims to produce valid and practical PISA-based numerical problems in the context of the pandemic period and to find out the role of the questions in the form of potential effects on the mathematical literacy skills of secondary school students. This research uses developmental research design, which has 2 stages, namely preliminary and formative evaluation (self-evaluation, expert review, one-to-one and small group validation, and field test). The participants in this study were students in Grade 8 who were under the age of 15 and different levels of skills. Data analysis was done descriptively by conducting observations, tests, interviews, and document analysis. The research was conducted face-to-face and via Zoom and WhatsApp Group (WAG) to produce valid and practical PISA-like arithmetic questions. Based on the students' responses, it can be stated that the questions presented are in the practical category because they can be completed quickly by students, they can be understood well by students, and they have the potential effect on students' mathematical literacy skills. In addition, there is a diversity of answers between one student and another according to the level of difficulty that is appropriate for Grade 8 students. This proves that a PISA-like numeration problem in the context of the religious day during a pandemic can help improve students' mathematical literacy.DOI : https://doi.org/10.22342/jpm.16.2.16010.157-170